2014
DOI: 10.1007/s11748-014-0377-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of surgical management for active mitral native valve infective endocarditis: a collective review of 57 patients

Abstract: Mitral valve repair is appropriate to prevent postoperative cardiac-related events. Reducing in-hospital mortality due to uncontrolled infection remains challenging. Early surgery may be reasonable for patients with small non-hemorrhagic infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Although previous systematic review [14] and reports from the western countries such as Ruttmann et al [15] and Solari et al [16] have shown significant survival benefits after mitral repair in comparison to replacement during active IE, in contrast, we could not clearly identify the same benefit-just trend toward better survival in repair group. These findings are almost the same as reports from eastern countries such as Miura et al [17] and Jung et al [18]. This suggests that survival differences could be from multifactorial factors including ethnics, underlying mitral etiology (rheumatic vs degenerative), timing of surgery, causative organism, and severity of infection.…”
Section: Discussionsupporting
confidence: 87%
“…Although previous systematic review [14] and reports from the western countries such as Ruttmann et al [15] and Solari et al [16] have shown significant survival benefits after mitral repair in comparison to replacement during active IE, in contrast, we could not clearly identify the same benefit-just trend toward better survival in repair group. These findings are almost the same as reports from eastern countries such as Miura et al [17] and Jung et al [18]. This suggests that survival differences could be from multifactorial factors including ethnics, underlying mitral etiology (rheumatic vs degenerative), timing of surgery, causative organism, and severity of infection.…”
Section: Discussionsupporting
confidence: 87%
“…It has been previously shown that IE patients undergoing MV replacement have increased early and late mortality when compared to MV repair . Patients in the MV repair group were older, required more emergency operations and more frequent and higher doses of inotropic support, and had a higher rate of severe cardiac decompensation . In our systematic review, the surgical acuity was higher in the mitral valve replacement group (91% vs 85%; P < 0.05).…”
Section: Discussionmentioning
confidence: 75%
“…The perioperative characteristics of the patients and the articles included in the analysis are summarized in Tables and . There were no randomized control trials comparing the two procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Anterior leaflet lesions, commissural lesions, extensive leaflet destruction and paravalvular abscess may require different and often complex techniques for MV repair [14]. Annuloplasty using a prosthetic ring provides coaptation of leaflets, limits tension in the suture, prevents further dilation of the annulus allowing a stable late surgical result [2, 6, 8].…”
Section: Discussionmentioning
confidence: 99%